Efficient removal of Cr (VI) using raw and phosphoric acid modified Sterculia Alata nutshell - Nawaz A.; Singh B.; Kumar P. (My University, 2025)
The adsorption behaviour of Cr (VI) onto raw Sterculia Alata nutshell (RSN) and phosphoric acid modified Sterculia Alata nutshell (PSN) from aqueous solution has been studied. Specific constraints such as initial pH (2-12), adsorbent dose (0.4-3.2 g/L) and temperature (24-32°C) have been investigated to examine the optimum process parameter for adsorption. Both the biosorbents are characterized based on their physicochemical characterization such as FTIR, SEM-EDS and XRD. The adsorption characteristics were assessed using the isotherms (Langmuir and Freundlich) to match the adsorption details. The maximum chromium adsorption capacity is obtained to be 39.89mg/g and 88.30mg/g for RSN and PSN at 28°C respectively. Both the biosorbents confirmed the aptness of pseudo second order kinetics throughout the chromium (VI) abstraction phase with R2 value greater than 0.99. © 2021, National Institute of Science Communication and Information Resources. All rights reserved.